The Effect of Dynamic Capabilities on MSMEs Digitalization: Exploring the Moderating Role of Firm Age - Adriana Amaya; Jose Campoverde; Maria Granda (Journal of Technology Management & Innovation, 2024)
Digitalization is changing the way that Micro, Small, and Medium Enterprises (MSMEs) adapt to survive in a turbulent environment. In this sense, certain capabilities are necessary to effectively identify opportunities to advance their technological adoption level. This paper seeks to provide a better understanding of how dynamic capabilities affect several aspects of the digital maturity of the firm. We employ a structural equation model to analyze how sensing and seizing capabilities affect the digitalization of MSMEs, taking advantage of a novel data set provided by the self-assessment tool Chequeo Digital in Ecuador. Our research focuses on dynamic capabilities in the MSMEs context, which represents a contribution due to the unique nature of these firms, enhancing our understanding of the effect of sensing and seizing on their digitalization level. The results show a positive and significant effect of sensing and seizing capabilities on the digitalization of MSMEs. Moreover, we found a negative and significant moderating effect of firm age, on the relationship between sensing capability and digitalization. The findings highlight the importance of an adequate process of identification and adoption of digital technologies that can be effectively applied in MSMEs. By developing sensing and seizing capabilities firms may take advantage of opportunities, and ultimately reconfigure the business to quickly adapt to the future advances of upcoming digital technologies.